Navigating the Tides of De-dollarization: Impact on Global Economy and BRICS Initiatives - Rana Al Mosharrafa (World Review of Political Economy)
This article examines the global economic shift away from US dollar dominance, focusing on the rise of the Chinese yuan and de-dollarization efforts, particularly by Russia and BRICS nations (Brazil, Russia, India, China, and South Africa). The study explores the dollar’s dominance since World War II and challenges it faced, including the Nixon Shock in 1971. The study’s significance is in investigating current de-dollarization trends, BRICS formation and implications, and their profound effects on the global economic ecosystem. The objective is to provide insights for policymakers, economists, businesses, and investors navigating an evolving international monetary landscape. The article explores the multifaceted process of de-dollarization, emphasizing the strategic shift away from the US dollar in international trade and finance. It analyzes challenges like time constraints, contractual obligations, and establishing financial infrastructure for transitioning to alternative currencies. Furthermore, the study discusses the formation of a proposed BRICS currency as a potential challenge to the dollar’s supremacy. The benefits and drawbacks of de-dollarization are explored, highlighting the potential impacts on global trade, national economies, and startups. Finally, it is important to emphasize the strategic advantages and risks of de-dollarization and advocate a well-calibrated approach to navigating the complexities of reshaping the global monetary landscape.